عصر حاضر میں جاسوسی کے جدید مظاہر و احکام: اسلامی قانون کا تجزیاتی مطالعہ: Contemporary Forms of Espionage and Their Legal Rulings: An Analytical Study in Islamic Law - Shehla Noor; Dr Abdul Rasheed (Al-Amīr Research Journal for Islamic Studies, 2025)
This study investigates the phenomenon of espionage as a fundamental component of state security in the contemporary world. Modern nation-states, particularly developed powers, employ a wide range of advanced techniques, tools, and methodologies to safeguard their territorial integrity against both internal and external threats. Within this context, the research focuses on three major areas. First, it explores the concept of espionage and its legal status in the light of the Qur’an and the Sunnah. Second, it examines the legal ruling concerning individuals who serve as spies, drawing upon Shariah discourse and the opinions of various schools of thought. Third, it analyzes the modern tools and techniques of espionage, their functions, and their expansion in the digital age. The rapid advancement of technology has transformed espionage beyond traditional intelligence gathering, incorporating cybersecurity surveillance, digital data extraction, electronic monitoring, and covert information manipulation. These developments present complex ethical and legal challenges for Muslim societies, necessitating a renewed engagement with classical Shariah-based jurisprudential principles. Drawing upon primary Islamic sources, including the Qur’an, the Sunnah, and classical juristic discussions. This study critically examines the boundaries between legitimate state security interests and the protection of individual privacy, human dignity, and communal trust. It further evaluates the circumstances under which espionage may be considered permissible, impermissible, or conditionally justified, considering contemporary security environments and international legal norms. By integrating classical Islamic doctrines with modern realities, this research offers a nuanced and contextually grounded Islamic legal perspective on the complicated phenomenon of espionage in the modern age. Keywords: Espionage, Shariah, Technology, Cyber Security, digital age.